Pertumbuhan Dan Hasil Tanaman Selada Merah (Lactuca Sativa L.) Akibat Pemberian Beberapa Takaran Kascing - Hayati Nurul Haq; Rahmawati Rahmawati; Chika Sumbari (Mahesa Research Institute, 2024)
Research in the form of a field experiment with the title